Workshop Pembelajaran Deep Learning dalam Meningkatkan Kualitas Pendidikan Sekolah Dasar di SD Negeri 3 Sandubaya - Musabihatul Kudsiah; Peni Lestari; Laelatul Kadriah; Sukma Para Sopi; Yatimatul Ummah; Muh. Nurul Maula (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This workshop on deep learning- based instruction aimed to enhance the quality of education by improving teacher’s ability to understand and implement deep learning approaches in the classroom. Conducted through a one-day direct mentoring session on November 1, 2025, the workshop involved teachers from SD Negeri 3 Sandubaya. The program introduced key concepts of deep learning, instructional design, and practucal development of learning activities that promote analytical thinking and creativity. Results indicated that approximately 60% of participants showed improved understanding of deep learning characteristics and were able to develop innovative lesson plans. Participant feedback was highly positive, highlighting the relevance and applicability of the material. The workshop also produced worksheets to support the design and implementation of deep learning-based instruction. Overall, the program contributed significantly the strengthening teachers’ competencies and enhancing student engagement.